A Comparative Evaluation of Search Engines on Finding Specific Domain Information on the Web - Azizan, Azilawati; Abu Bakar, Zainab; Abd Rahman, Nurazzah; Masrom, Suraya; Khairuddin, Nurkhairizan (International Journal of Engineering and Technology, 2018)
Recently search engines have provided a truly amazing search service, especially in finding general information on the Web. However, the question arises, does search engine perform the same when seeking domain specific information such as medical, geographical or agriculture information? Along with that issue, an experiment has been conducted to test the effectiveness of todayâ€™s search engines from the aspect of information searching in a specific domain. There were four search engines have been selected namely Google, Bing, Yahoo and DuckDuckGo for the experiment. While for the domain specific, we chose to test information about the popular fruit in Southeast Asia that is durian. Precision metric has been used to evaluate the retrieval effectiveness. The findings show that Google has outperformed the other three search engines. Nevertheless, the mean average precision value 0.51 given by Google is still low to be satisfied neither by the researcher nor the information seekers.Â Â